Dendritic Subglacial Drainage Systems in Cold Glaciers Formed by Cut‐and‐Closure Processes. Issue 4 (2nd September 2014) - Naegeli, Kathrin; Lovell, Harold; Zemp, Michael; Benn, Douglas I.
Abstract The routing and storage of meltwater and the configuration of drainage systems in glaciers exert a profound influence on glacier behaviour. However, little is known about the hydrological systems of cold glaciers, which form a significant proportion of the total glacier population in the climate sensitive region of the High Arctic. Using glacio‐speleological techniques, we obtained direct access to explore and survey three conduit systems and one moulin within the tongue area of Tellbreen, a small cold‐based valley glacier in central Spitsbergen. More than 600 m of conduits were surveyed and mapped in plan, profile and cross‐section view to analyse the configuration of the drainage system. The investigations revealed that cold‐based glaciers can exhibit a dendritic drainage network with supra‐, en‐ and subglacial components formed most likely by cut‐and‐closure processes as well as surface‐to‐bed drainage via moulins. Furthermore, we observed that water is stored within the glacier and released gradually via subglacial conduits during the winter months, forming a large and active icing in the proglacial area. The presence of supra‐, en‐ and subglacial components, the surface‐to‐bed moulin and the dendritic subglacial drainage network suggest that existing models and understanding of the hydrology of cold glaciers needs to be re‐evaluated, mostly concerning the different possible pathways and processes that form the hydrological system.